Forget me not [videorecording (DVD)] (Cinema Libre Studio, 2022)
As three-year-old Emilio prepares to start school, his family finds itself embroiled in the challenge all too common for children with disabilities, to secure the right to inclusive education. Cornered in one of the most segregated education systems, New York City public schools, filmmaker Olivier and his wife Hilda turn to the camera on themselves and their child with Down Syndrome as they navigate a system originally designed to silo children with disabilities. Emilio₂s parents learn from the personal stories of students and their parents who have fought for inclusion against the injustices built into the education system as they continue to fight for Emilio₂s future. It reveals a path to a more inclusive society that starts with welcoming diversity in the classroom.